Detection of 12 Common Food-Borne Bacterial Pathogens by TaqMan Real-Time PCR Using a Single Set of Reaction Conditions - Liu, Ying; Cao, Yang; Wang, Tao; Dong, Qingyang; Li, Junwen; Niu, Chao (Frontiers in Microbiology, 2019)
Food safety has become an important public health issue worldwide. However, conventional methods for the detection of food-borne pathogens are complicated, and time-consuming. Moreover, the sensitivity is often low, and it is difficult to achieve high-throughput detection. In this study, we developed a TaqMan real-time polymerase chain reaction (PCR) assay for the simultaneous detection and quantification of 12 common pathogens in a single reaction, including Escherichia coli O157:H7, Listeria monocytogenes, Salmonella enterica, Vibrio parahaemolyticus, β-streptococcus hemolyticus, Yersinia enterocolitica, Enterococcus faecalis, Shigella spp., Proteus spp., Vibrio fluvialis, Staphylococcus aureus, and Campylobacter jejuni in food and drinking water. Based on published sequence data, specific primers and fluorescently-labeled hybridization probes were designed based on the virulence genes of the 12 pathogens, and these primers and probes were optimized to achieve consistent reaction conditions. The assay was assessed using a list of 105 well-defined intestinal bacterial strains or isolates. No cross reactivity between the different pathogens was observed. The analytical sensitivity was 1 copy/μL for Escherichia coli O157:H7, Listeria monocytogenes, β-streptococcus hemolyticus, Shigella spp., Proteus spp., and Vibrio fluvialis, 10 copies/μL for Salmonella enterica, Vibrio parahaemolyticus, Yersinia enterocolitica, Enterococcus faecalis, Staphylococcus aureus, and Campylobacter jejuni, respectively. The limit of detection (LOD) was 296, 500, 177, 56, 960, 830, 625, 520, 573, 161, 875 and 495 CFU/mL for Escherichia coli O157:H7, Listeria monocytogenes, Salmonella enterica, Vibrio parahaemolyticus, β-streptococcus hemolyticus, Yersinia enterocolitica, Enterococcus faecalis, Shigella spp., Proteus spp., Vibrio fluvialis, Staphylococcus aureus, and Campylobacter jejuni, respectively. The limit of accurate quantification for the assay in meat samples was 103 CFU/g for Vibrio parahaemolyticus and 104 CFU/g for other 11 strains. Together, these results indicate that the optimized TaqMan real-time PCR assay has the potential to be used for routine detection of pathogenic bacteria due to its rapid analysis time, low cost, high-throughput, high specificity and sensitivity.